2018
DOI: 10.1155/2018/4505191
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Meditation Targets Transdiagnostic Symptoms Implicated in Stress‐Related Disorders: Understanding Relationships between Changes in Mindfulness, Sleep Quality, and Physical Symptoms

Abstract: Mindfulness-Based Stress Reduction (MBSR) is an 8-week meditation program known to improve anxiety, depression, and psychological well-being. Other health-related effects, such as sleep quality, are less well established, as are the psychological processes associated with therapeutic change. This prospective, observational study (n = 213) aimed to determine whether perseverative cognition, indicated by rumination and intrusive thoughts, and emotion regulation, measured by avoidance, thought suppression, emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 45 publications
(56 reference statements)
2
39
1
Order By: Relevance
“…Participating in sleep research may also have triggered self-monitoring behavior and reactivity (Kazdin 1974) in both groups, which could account for the improvements seen in the waitlist participants (Todd and Mullan 2014). In the context of prior studies, the null finding in this experiment suggests that improving subjective sleep quality in a meaningful way may require longer (Black et al 2015;Britton et al 2010;Greeson et al 2018) or more targeted interventions (Ong et al 2014).…”
Section: Subjective Sleep Quality Improved In Both Experimental Groupsmentioning
confidence: 75%
See 2 more Smart Citations
“…Participating in sleep research may also have triggered self-monitoring behavior and reactivity (Kazdin 1974) in both groups, which could account for the improvements seen in the waitlist participants (Todd and Mullan 2014). In the context of prior studies, the null finding in this experiment suggests that improving subjective sleep quality in a meaningful way may require longer (Black et al 2015;Britton et al 2010;Greeson et al 2018) or more targeted interventions (Ong et al 2014).…”
Section: Subjective Sleep Quality Improved In Both Experimental Groupsmentioning
confidence: 75%
“…In the SENSE study, Blake et al (2017) showed that both somatic and cognitive arousal (measured by the PSAS) were mediators of change in four key outcome variables (objective SOL, subjective SE, PSQI global score, and anxiety). A recent study (Greeson et al 2018) showed that unwanted intrusive thoughts and thought suppression, both constructs related to cognitive arousal, each accounted for a significant portion of the negative correlation between change in mindfulness and change in sleep disturbance following an 8-week mindfulness intervention. Our own findings are well in line with these results.…”
Section: Pre-sleep Cognitive Arousal Improved and Was Associated Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive arousal has been associated with poor and disrupted sleep, and the coping behaviors people use to combat this arousal are important to a person's sleep quality [24]. Cognitive arousal can manifest into anxiety and depression, which is attributed to stress, and unmanaged stress can lead to sleep problems [12].…”
Section: Coping: Intrusiveness Avoidance Arousal and Sleep Qualitymentioning
confidence: 99%
“…Emotion regulation is a process that occurs in stages and usually has genetic and biological components, but emotion regulation may be improved with practice or training [8][9][10][11]. One influential technique for promoting emotion regulation and self-awareness is mindfulness meditation and related therapies [10,12,13]. In a related study, Thompson & Waltz (2010) [14] surveyed 378 undergraduates on self-report measures of PTSD, mindfulness, experiential avoidance, thought suppression, and avoidance coping.…”
Section: Introductionmentioning
confidence: 99%